Tagasaste (Chamaecytisus Palmensis) Leaf Supplementation to Enhance Nutrient Intake and Production Performance of Sheep in the Ethiopian Highlands - International Livestock Research Institute; Hawassa University (International Food Policy Research Institute, 2019)
Tree Lucerne (Chamaecytisus palmensis) is a multipurpose fodder tree that grows very well in cooler highlands of Ethiopia and can serve as a source of high-quality protein supplement for farm animals. Despite its potential, the level of adoption and utilization is very limited. Africa RISING project in the Ethiopia highlands has conducted action research on tree Lucerne to fill knowledge gaps and promote its adoption. To recommend optimal level of use of the foliage, a feeding experiment was conducted using yearling Menz sheep. The experiment involved graded levels of tree Lucerne hay supplementation (100 g, 200 g, 300 g, and 400 g/day) to sheep fed barely straw basal diet ad libitum. The feeding trial lasted for 90 days followed by 7 days of digestibility trial and carcass evaluation. Data were generated on feed intake, nutrient digestibility, body weight gain, and carcass quality for the different treatments.